2019
DOI: 10.1186/s12874-019-0688-x
|View full text |Cite
|
Sign up to set email alerts
|

Tools used to assess the quality of peer review reports: a methodological systematic review

Abstract: Background A strong need exists for a validated tool that clearly defines peer review report quality in biomedical research, as it will allow evaluating interventions aimed at improving the peer review process in well-performed trials. We aim to identify and describe existing tools for assessing the quality of peer review reports in biomedical research. Methods We conducted a methodological systematic review by searching PubMed, EMBASE (via Ovid) and The Cochrane Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 52 publications
0
60
0
Order By: Relevance
“…In a recent study (2019) by Superchi et al that systematically reviewed tools used by journal editors to assess the quality of peer-review reports, the authors identified nine quality domains pertaining to peer-reviewer skills, of which five (ie, relevance and originality of the study, interpretation of study results, strength and weaknesses, manuscript presentation and organisation) arguably overlap with the skillset of authors. The remainder are directly concerned with skills related to structure and delivery of the peer-review report,27 which we believe may not automatically follow from being a prolific author. Therefore, we propose that the following four domains can, and in principle should, be taught to prospective reviewers: (1) structure of the reviewer’s comments; (2) characteristics of reviewers’ comments, including concepts such as clarity, constructiveness, detail/thoroughness, fairness, knowledgeability and tone; (3) timeliness of the review report; and (4) usefulness of the review report to editorial decision making and manuscript improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (2019) by Superchi et al that systematically reviewed tools used by journal editors to assess the quality of peer-review reports, the authors identified nine quality domains pertaining to peer-reviewer skills, of which five (ie, relevance and originality of the study, interpretation of study results, strength and weaknesses, manuscript presentation and organisation) arguably overlap with the skillset of authors. The remainder are directly concerned with skills related to structure and delivery of the peer-review report,27 which we believe may not automatically follow from being a prolific author. Therefore, we propose that the following four domains can, and in principle should, be taught to prospective reviewers: (1) structure of the reviewer’s comments; (2) characteristics of reviewers’ comments, including concepts such as clarity, constructiveness, detail/thoroughness, fairness, knowledgeability and tone; (3) timeliness of the review report; and (4) usefulness of the review report to editorial decision making and manuscript improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This could then also be used to create standardised peer review 'check-lists' to help guide reviewers through the process. Research and development of tools for measuring the quality of peer review are only in their relative infancy [82], and even then focused mostly on disciplines such as biomedicine [88].…”
Section: Functionality and Quality Of Peer Reviewmentioning
confidence: 99%
“…Editors must be vigilant and if allowed by their journal, screen such comments immediately. Finally, a variety of tools have been created to assess the quality of peer reviews, refer to Superchi, González [ 12 ] for a detailed review. Our coding structure offers one such method to evaluate reviewer behaviour.…”
Section: Discussionmentioning
confidence: 99%